Regulatory networks of the F-box protein FBX206 and OVATE family proteins modulate brassinosteroid biosynthesis to regulate grain size and yield in rice - Sun, Xiaoxuan (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.